Relationship between Motivation for Participating in the Extension Program and the Performance of the Members of the Bungo Cangkiang Farmer Group in Padang Pariaman Regency - Dinda Septiadi; Tasril Bartin (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the low performance of members of the Bungo Cangkiang farmer group in Padang Pariaman Regency, this is alleged because it has to do with the motivation to follow the agricultural counseling program. This study aims to look at the motivational picture of participating in the extension tile program, the performance picture of farmer group members, and the relationship between the motivation to follow the counseling program and the performance of members of the Bungo Cangkiang farmer group in Padang Pariaman Regency. The approach to this research is quantitative with a descriptive type of correlational research. The research population is a member of Bungo Cangkiang farmer group in Padang Pariaman regency as many as 52 people and the sample was taken as much as 75% of 39 people, with the technique of sampling is random sampling stratified. In this research, the data collection techniques used are questionnaires and tools used, namely questionnaires. Data analysis techniques using percentage formulas and product moment formulas. The results of this study showed that: 1) the motivation to participate in the counseling program of farmer group members is relatively low; 2) the performance of farmers group members is relatively low; 3) There is a significant relationship between the motivation to participate in the counseling program and the performance of members of the Bungo Cangkiang farmer group in Padang Pariaman Regency. It is expected that the extension of field agriculture (PPL) to be more sensitive to the formation of motivation and improvement of the performance of members of the Bungo Cangkiang farmer group.Keywords: Motivation, Program Counseling, Performance